2018
DOI: 10.3762/bjnano.9.19
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of a bisimidazolium salt with dodecyl sulfate anion doped with carbon nanotubes

Abstract: A new bisimidazolium salt with dodecyl sulfate as counterion has been designed and prepared. This salt shows a SmA phase that is stable at room temperature. The new ionic liquid crystal (ILC) was characterized by 1H NMR, 13C NMR and IR spectroscopy. Its liquid crystalline properties were analyzed by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and powder X-ray diffraction (XRD) studies. The dielectric spectra of the ILC doped with different concentrations of carbon nanotubes (CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Cherian et al [89] have very recently reported parallel conductivities of 10 - hydrogen sulfate. These values are like those shown here, and are superior to some state-of-theart polymerized ionic liquid electrolytes [90], and comparable to phosphonium or imidazoliumbased ionic liquids (10 -2 S cm -1 , at 30 o C) and to dicationic imidazolium salts forming SmA phases (10 -6 to 10 -4 S cm -1 , near room temperature) [91][92][93].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 81%
“…Cherian et al [89] have very recently reported parallel conductivities of 10 - hydrogen sulfate. These values are like those shown here, and are superior to some state-of-theart polymerized ionic liquid electrolytes [90], and comparable to phosphonium or imidazoliumbased ionic liquids (10 -2 S cm -1 , at 30 o C) and to dicationic imidazolium salts forming SmA phases (10 -6 to 10 -4 S cm -1 , near room temperature) [91][92][93].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 81%
“…In several reports on this and analogous materials, the layered mesophases were assigned as smectic A 6,[8][9][10] . We note that in work Yang et al 7 the mesophase of C 6 (C 12 im) 2 Br 2 was designated as smectic C phase, but it probably concerns smectic A phase as reported by Bara et al 6 The mesophase assignment as smectic C phase in this material was questioned in the review 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There are several types such as ammonium, imidazolium, pyridinium based ILCs reported, among these monocationic imidazolium-based salts are the most studied ones 4 . Recently, dicationic ionic liquid crystals (DILCs) have also been presented [5][6][7][8][9][10][11] . DILCs are composed of a dication containing two single-charged ions covalently linked by a spacer, and single-charged anions 5 .…”
Section: Ionic Liquids Crystals Belong To a Special Class Of Ionic LImentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst having alkyl terminations still fall some orders of magnitude below those exhibited by reference phosphonium or imidazolium-based ionic liquid electrolytes (10 −2 S•cm −1 ) [60,61], we found that the presence of oxyethylene groups promotes high conductivities in the 10 −1.5 S•cm −1 range, comparable to those required in commercial batteries or fuel cells [48,49]. The presence of additional polar sites in these terminations may be the key to facilitate long-range transport in these materials.…”
Section: Discussionmentioning
confidence: 96%